2023
DOI: 10.21203/rs.3.rs-2521636/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Emotional Intelligence and Organizational Commitment among Nurses Working in Governmental Hospitals in Jordan

Abstract: Introduction: Nurses' emotions and feelings in response to their environment and their ability to manage their own emotions can have significant consequences on several aspects of their job. In Jordan, studies are still investigating whether emotional intelligence is significantly related to organizational commitment. Aim To investigate whether a significant relationship exists between emotional intelligence and organizational commitment among Jordanian nurses working in governmental hospitals in Jordan. Met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[17] Previous studies have also found similar results, indicating the universal importance of emotional intelligence in the nursing profession. [18,19] The justification for these findings can be supported by the growing recognition of emotional intelligence as a vital competency in healthcare settings. [20][21][22] Researches have consistently demonstrated that nurses with higher emotional intelligence exhibit better job performance [23,24] and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Previous studies have also found similar results, indicating the universal importance of emotional intelligence in the nursing profession. [18,19] The justification for these findings can be supported by the growing recognition of emotional intelligence as a vital competency in healthcare settings. [20][21][22] Researches have consistently demonstrated that nurses with higher emotional intelligence exhibit better job performance [23,24] and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%